L' humanisme agissant de Karl Marx - Somerhausen, Luc (Paris : Richard-Masse, 1946)
Bibliotheek Camille Huysmans
Dedicator: Somerhausen, Luc, dedicatee: Huysmans, Camille
Frans
Monografie
Keywords: Marx, Karl; utopisme